Implementasi Prinsip Squash and Stretch dalam Menciptakan Ekspresi Wajah Karakter Animasi Murdasa - I Gede Adi Sudi Anggara; Sutarwiyasa, I Ketut; Ariputri, Ni Putu Arliana Fitriya (Institut Bisnis dan Teknologi Indonesia, 2024)
This study aims to implement the squash & stretch principle through rigging methods to create various facial expressions on the animated character Murdasa. Using a qualitative experimental approach, this research visually observes how the deformation of facial elements, such as eyes, mouth, and eyebrows, generates dynamic and emotional expressions. Squash & stretch techniques were applied to several expressions, including happiness, sadness, anger, surprise, and disappointment. Visual observation revealed that squash conveys pressure and emotional intensity, while stretch emphasizes openness and expansion of expression. This approach provides deep insights into the process of creating facial expressions in animation and produces an expression library sheet that facilitates animators in efficiently creating a wide range of expressions. The findings demonstrate that the squash & stretch principle significantly contributes to the development of lively and emotionally engaging animated characters.